A critical insight into the identity authentication systems on smartphones - Tehseen Mehraj; Mir Aman Sheheryar; Sajaad Ahmed Lone; A. H. Mir (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
The advancement of computing power on mobile devices and their popularity among people in performing sensitive data exchange is uncovering an urgent need for a highly secure solution than the existing ones. The need for such a security solution persists that should be able to thwart not only the contemporary threats but also offer continued support without bowing down to progression in technology. Though some security solutions have been contemplated, a lack of standardised or absolute security solution which can provide a feasible and secure solution to mobile phones exists. In this paper, a survey based on various biometric and non-biometric access management schemes has been performed. The copious solutions put forward by researchers so far were discovered to fail in traits like user adaptability and efficiency. Each of the works put forward by various researchers has been single-handedly contemplated followed by analysis. Ultimately, open problems and challenges were inferences from the survey conducted.